The business of slavery and the rise of American capitalism, 1815-1860 - Schermerhorn, Calvin, 1975- (EBSCO Academic Collection, 2015)
"Focuses on networks of people, information, conveyances, and other resources and technologies that moved slave-based products from suppliers to buyers and users." (page 3) The book examines the credit and financial systems that grew up around trade in slaves and products made by slaves.